Dating the Aterian using techniques of luminescence dating and implications for mapping the dispersal of modern Homo sapiens - Clark-Balzan, LA (2013)
The Aterian is a Middle Stone Age technocomplex that occurs throughout North Africa, typically identified by the presence of pedunculates. Due to widespread radiocarbon dating of contaminated samples, most Aterian sites are not well-dated. The use of more appropriate absolute dating techniques, including optically stimulated luminescence (OSL), has renewed interest in the Aterian technocomplex--several sites with remarkable behavioural innovations have been the source of surprisingly early ages.